2010
DOI: 10.5012/bkcs.2010.31.04.1077
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Syntheses, Structures, and Characterizations of Two Lanthanide Sulfate Hydrates Materials, La2(SO4)3·H2O and Eu2(SO4)3·4H2O

Abstract: Two-or three-dimensional framework materials containing rich structural diversities are of continuous interest attributable to their technologically important properties and potential applications such as catalysis, ion-exchange, adsorption, intercalation, and radioactive waste remediation. [1][2][3][4] Materials showing these functional features are normally composed of structurally versatile cations. Heavier metal cations with larger coordination spheres and cations exhibiting ability to accommodate other po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…For this reason, in complex compounds, it is difficult to clearly determine the relation between the coordination and spectroscopic parameters of Eu 3+ ions in the host lattice. In such a situation, the compounds with a stoichiometric content of europium ions have attracted the increasing attention of researchers [37,38,[47][48][49][50][51][52][53]. Self-activated phosphors are characterized by an almost complete absence of structural defects, and the precise determination of the crystal structure makes it possible to evaluate the relations between the Eu 3+ ion coordination in the lattice and spectroscopic characteristics of the compound.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, in complex compounds, it is difficult to clearly determine the relation between the coordination and spectroscopic parameters of Eu 3+ ions in the host lattice. In such a situation, the compounds with a stoichiometric content of europium ions have attracted the increasing attention of researchers [37,38,[47][48][49][50][51][52][53]. Self-activated phosphors are characterized by an almost complete absence of structural defects, and the precise determination of the crystal structure makes it possible to evaluate the relations between the Eu 3+ ion coordination in the lattice and spectroscopic characteristics of the compound.…”
Section: Introductionmentioning
confidence: 99%
“…Simple europium stoichiometric compounds with tetrahedral MO 4 units, where M = Mo, W and S, were thoroughly studied and their applicability as highly efficient polyfunctional materials was shown [54][55][56][57][58][59][60][61][62][63][64][65][66][67]. At the same time, the properties of complex compounds of monovalent cations and rare-earth elements with tetrahedral anions are presented quite sporadically in the literature [37,[48][49][50][51]53,[68][69][70][71][72]. The structures and some properties of several double molybdates and tungstates with general composition AEu(MO 4 ) 2 (A = Li, Na, K, Cs, Rb, Ag + ; M = Mo, W) were investigated in the past and the examples of such contributions can be found elsewhere [72][73][74][75][76].…”
Section: Introductionmentioning
confidence: 99%
“…In the past, several studies were devoted to the synthesis and characterization of europium (III) sulfate, and it was shown that the preparation of Eu2(SO4)3 is a nontrivial task because of high a tendency to hydration [13,[35][36][37][38]. The available structural properties of the presently known Eu 3+ sulfate hydrates are listed in Table S2 [20,35,[39][40][41][42][43]. Nevertheless, to the best of our knowledge, the crystal structure and basic physical properties of anhydrous Eu2(SO4)3 are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In both tetrahedra the O-S-O angles are different from the ideal tetrahedral angle and vary within 102-121°, and that leads to a significant deforming of tetrahedra. The sulfate tetrahedra in europium (III) sulfate have much more deformation in comparison with the tetrahedra in the structures of europium sulfates crystallohydrates[20,35,[39][40][41][42][43], apparently, because of a higher anhydrous sulfate structure rigidity.…”
mentioning
confidence: 99%
“…Lanthanum sulfate enneahydrate, La 2 (SO 4 ) 3 $9H 2 O, is the most common hydrate of lanthanum sulfate, La 2 (SO 4 ) 3 $nH 2 O (n ¼ 1-9) [1][2][3] and is the only stable hydrate in contact with its solution between 0 and 100 . La 2 (SO 4 ) 3 is sparingly soluble at room temperature and the solubility diminishes with temperature.…”
Section: Introductionmentioning
confidence: 99%